Podział wielowymiarowej przestrzeni zmiennych a modele hybrydowe - Gatnar, Eugeniusz (Multidimensional Feature Space Partition and Hybrid Models, 2009)
Hybrid models are based on the recursive partitioning of multidimensional feature space into sub-spaces (regions). Then, in each segment a local model is built (e.g. linear model) and finally all the local models are combined into the global model. The aim of the paper is to discuss the results of application of different hybrid models in regression. The author compares the goodness of fit of the models to the training data. The paper also presents the portions of code of the R statistical package used in the author's experiments
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 20-30